The evolution of the Internet of Things (IoT) over the past 20 years. (May 2021) - Wang, Jianxin; Lim, Ming K.; Wang, Chao; Tseng, Ming-Lang
Abstract: To reveal the origin of the IoT, evaluate its mainstream research topics, and discuss the challenges facing the IoT in the future, this paper conducts a bibliometric study of the IoT from 2000 to 2019. First, this paper presents a basic bibliometric overview of the IoT. Second, co-citation, coupling and cluster analysis methods are used to analyse collaboration networks, and VOSviewer is used to visualize the networks. Third, biblioshiny is used to analyse the thematic trends of IoT. Finally, this paper discusses IoT challenges and provides some suggestions to address them. The limitations of this paper are also summarized. Research results show that, the mainstream studies in this field mainly focus on IoT security, wireless sensor networks, IoT management, IoT challenges and privacy. In addition, the thematic evolution of keywords shows that security and algorithm issues have become basic themes in the field of IoT research in recent years.